Catatan Tentang Gaya Seni Relief di Candi Simangambat, Kabupaten Mandailing Natal, Provinsi Sumatera Utara - Andri Restiyadi (Balai Arkeologi Sumatera Utara, 2010)
AbstractRelief art style that can be interpreted as a redundancy to a certain style, at certain times and places can be used as an indication for the presence of outside influences that affect a work relief. In addition, by comparing the art style can be a relative dating to the building of the temple, in this case is a temple in Simangambat, North Sumatera.